Innovative Techniques for Measuring the Oil Content of Oil‐Contaminated Porous Media. Issue 3 (16th July 2019) - Zheng, Tianyuan; Zheng, Xilai; Wang, Huan; Xin, Jia; Zhang, Bo; Walther, Marc
Abstract: The oil content of oil‐contaminated porous media is an important parameter for the assessment and remediation of oil pollution in soil and groundwater. However, an accurate measurement method is not available. In this study, we propose a new equation to calculate the oil content of water‐bearing media based on traditional extraction–ultraviolet spectroscopy. Further, an improved experimental method was developed. The results indicate that the pure solid weight and oil content of oil‐contaminated media can be accurately determined by introducing the oil drying loss coefficient (γ). The average relative errors of the improved method range from −0.14% to −0.96%. They are much smaller than errors of −4.49% to −10.97% of the original methods, indicating that the accuracy of measured oil content is enhanced. In addition, the accuracy of the new method does not depend on oil volatility and oil content.